Gastric epithelioid haemangioendothelioma: a rare cause of upper gastrointestinal bleeding - Sanjay, P (BMJ Group, 2005)
Vascular tumours of the stomach are rare, representing 0.9%–3.3% of all gastric neoplasms. A 58 year old man was admitted as an emergency with a one day history of haematemesis and melaena. He underwent an emergency laparotomy for a tumour in the lesser curve of the stomach. The tumour showed the characteristic histological and immunohistochemical features of epithelioid haemangioendothelioma. Surgery in the form of wide excision seems to be the treatment of choice for this rare neoplasm. This case highlights the difficulty in diagnosing this rare tumour preoperatively and emphasises the need for long term follow up in view of its uncertain metastatic potential.